2021
DOI: 10.1111/imm.13373
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 dimer‐specific ligands selectively activate protein kinase C isoforms in Leishmania infection

Abstract: Of the thirteen Toll-like receptors (TLRs) in mice, TLR2 has a unique ability of forming heterodimers with TLR1 and TLR6. Such associations lead to selective cellular signalling and cellular responses such as cytokine expression. One of the signalling intermediates is protein kinase C (PKC); of which, eight isoforms are expressed in macrophages.Leishmania-a protozoan parasite that resides and replicates in macrophages-selectively modulates PKC-α, PKC-β, PKC-δ and PKC-ζ isoforms in macrophages. As TLR2 plays si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Cumulatively, the results connect TLR2 with TPL2 in the signalling chain. Visceral leishmaniasis has reported TLR2 mediated TNF‐α production as well as our lab has reported TLR2‐induced IL‐12 expression upon stimulation [36, 37]. In current work, with L. donovani infection the TLR2 blocking did not essentially affect either the pro‐inflammatory cytokine gene expression spike or the IL‐10 expression, rather did severely impair the TGF‐β expression.…”
Section: Discussionmentioning
confidence: 46%
“…Cumulatively, the results connect TLR2 with TPL2 in the signalling chain. Visceral leishmaniasis has reported TLR2 mediated TNF‐α production as well as our lab has reported TLR2‐induced IL‐12 expression upon stimulation [36, 37]. In current work, with L. donovani infection the TLR2 blocking did not essentially affect either the pro‐inflammatory cytokine gene expression spike or the IL‐10 expression, rather did severely impair the TGF‐β expression.…”
Section: Discussionmentioning
confidence: 46%
“… 33 We first found that K + concentration had no effect on the HCC cell viability ( online supplemental figure S4G ). We then used the TLR2 ligand Pam3CSK4 34 to stimulate the Huh7-GSDMD cells with or without KCl. The results found that KCl itself might not induce IFN-β after the stimulation of Pam3CSK4 ( online supplemental figure S4H ).…”
Section: Resultsmentioning
confidence: 99%
“…Cysteine proteases are omnipresent enzymes that are critically implicated in the pathogenesis of protozoic infections. Despite their significance, cysteine proteases as therapeutic targets have not yet been translated into clinical practice [36,37]. Both parasite and host proteinases are involved in the clinical manifestation of leishmaniasis [38].…”
Section: Discussionmentioning
confidence: 99%